“E poi in Roma ognuno è Aretino”: Pasquino, Aretino, and the Concealed Self - Faini, Marco (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
This article explores Pietro Aretino’s pasquinade production as a crucial phase in the construction of his public and literary persona that is characterized by a peculiar effacement of the author’s voice. The article then focuses on issues of anonymity and authorship in the fifteenth and sixteenth centuries, with special attention devoted to the connections between the pasquinade and Burchiellesque traditions and the idea of the author that emerges from them. In particular, the article reflects on ideas of the mask, and of literature as a game in which pre-existing materials are ceaselessly reassembled. These views are ultimately reconnected to a sceptical view of reality as fundamentally ungraspable.